Socialization The Three Big Sins of Education to Include Character Values - Viviana Murni; Yuliana Fontania; Rufina Arsenia Agung; Ferdinandus Ardian Ali (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The world of education is experiencing challenges with the three big sins of education, namely bullying, sexual violence and intolerance. One effort to prevent this is socialize the three major sins to students. The aimed of this activity is to instill character values ​​in students, so that they do not become perpetrators of these 3 major sins. The methods used in this activity were lectures and the practice of making posters refusing to commit the three major educational sins. This activity was carried out through several stages, namely preparation in the form of survey, implementation, and evaluation. The survey results provide an overview of one of the needs of the Lawir parish, namely the socialization of the three principles of education at the elementary school level, so the team carried out the outreach to 40 students at SDI Lawir. Socialization activities filled with lectures and poster making practices can increase the instilling of character values ​​in students. This activity ends with an evaluation, namely making observations to measure the level of success of socialization activities for the three big sins of education. The evaluation results shown that the average achievement of each community service indicator obtained an average of 91.80 (very good), meaning that the socialization of the 3 major sins contributed positively to the development of character values ​​in students.